2012
DOI: 10.1097/mao.0b013e318254ec24
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of the Semicircular Canals With Preservation of Hearing and Rotational Sensitivity

Abstract: Hypothesis It is possible to implant a stimulating electrode array in the semicircular canals without damaging rotational sensitivity or hearing. The electrodes will evoke robust and precisely controlled eye-movements Background A number of groups are attempting to develop a neural prosthesis to ameliorate abnormal vestibular function. Animal studies demonstrate that electrodes near the canal ampullae can produce electrically-evoked eye movements. The target condition of these studies is typically bilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 22 publications
0
47
1
4
Order By: Relevance
“…Previous studies (e.g., Rubinstein et al 2012) demonstrated that natural vestibular rotational sensitivity could be preserved in the short term following implantation of a vestibular neurostimulator in monkeys when the electrode placement and design maintained the patency of the lumen of the implanted semicircular canal. This finding was not replicated in human subjects with a diseased ear prior to implantation Golub et al 2014).…”
Section: Preexisting Peripheral Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (e.g., Rubinstein et al 2012) demonstrated that natural vestibular rotational sensitivity could be preserved in the short term following implantation of a vestibular neurostimulator in monkeys when the electrode placement and design maintained the patency of the lumen of the implanted semicircular canal. This finding was not replicated in human subjects with a diseased ear prior to implantation Golub et al 2014).…”
Section: Preexisting Peripheral Lossmentioning
confidence: 99%
“…Implantable, single-and multi-channel vestibular neurostimulators, which deliver trains of biphasic pulses to afferents of individual branches of the ampullar nerves innervating the three semicircular canals, have been extensively studied in animal models, particularly non-human primates, using devices developed by several groups (Davidovics et al 2011;Della Santina et al 2005Gong et al 2008;Dai et al 2011a, b;Lewis et al 2001Lewis et al , 2002Lewis et al , 2010Nie et al 2013;Phillips et al 2011Phillips et al , 2012Phillips et al , 2015bRubinstein et al 2012). This type of electrical stimulation has long been known to modulate the behavior of vestibular afferents (Goldberg et al 1984) and to elicit eye movements Cohen and Suzuki 1963;Suzuki and Cohen 1964) comparable to those produced by the angular vestibulo-ocular reflex (aVOR).…”
Section: Introductionmentioning
confidence: 99%
“…By delivering biphasic, symmetric, charge-balanced, rate-modulated pulses, the device generated partly compensatory eye movements for head rotations about the gyro's axis of rotational sensitivity. Wall, Guyot, and colleagues have applied a similar approach to single-channel vestibular nerve stimulation in humans (Wall et al 2007;Guyot et al 2011aGuyot et al , b, 2012, and Nie, Phillips, Rubinstein, and colleagues have recently applied analogous technology to monkeys and a human subject as part of an effort to develop a vestibular pacing device for treatment of Ménière's disease (Nie et al 2011;Rubinstein et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Şimdiki çalışmalar VOR in oluşturulması için uygun elektik stimulasuyon modelini bulmak ve VOR' deki adaptif mekanizmaları geliştirmek üzerine odaklanmıştır (56). Kulakta bulunan saç hücrelerinin yenilenmesini teşvik etmek için geliştirilen vestibuler protezler, genetik olarak gentamisin duyarlılığnın tespiti, kulaktaki saçlı hücre kaybı için alfa lipoik asit coenzyme Q10 gibi anti oksidan kullanımı gündemde olan tedavilerdir (57,58).…”
Section: İki Tarafli Vestibulopatide Vestibuler Rehabilitasyonunclassified